The Archaeology of German and British Colonial Entanglements in Kpando-Ghana - Apoh, W. (International Journal of Historical Archaeology, 2013)
In talking about the cultural diversity of Africa's past, the archaeological assessment of West African sites with mangled tangible and intangible fragments of German and British and/or French colonial encounters should not be ignored but rather discussed. This research explores how specific daily material cultural practices of German and British colonizers and Kpando indigenes in the Volta Region of Ghana were enmeshed in a medley of geopolitical, ideological and exchange connections. Through the use of archaeological, archival and ethnographic sources, this paper examines how daily practices of the people of Kpando were impacted by pre-colonial and dual colonial political economic pressures from the seventeenth through the twentieth centuries. This paper archaeologically explores how colonial officials maintained and renegotiated the norms of domesticity/gentility/Europeaness in their encounter with Akpini domestic technology, foodways and cultural practices. © 2013 Springer Science+Business Media New York.
Keywords: Entangled archaeology; German and British colonialism; Kpando-Ghana